Efektivitas Media Booklet terhadap Sikap Anak Sekolah Dasar dalam Penanganan Kecemasan Kegawatdaruratan Fraktur Gigi - Rifa Fauziah; Siti Nurlela; Aditya Nurrochman (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2026)
One of the problems that often occurs in children is dental fracture emergencies, rationally 5.4% of the incidence of injuries at school, the prevalence of school children who experience injuries is 13% at the age of 5-14 years. In emergency situations, children often experience anxiety that can worsen their emotional condition. Efforts that can be made to reduce anxiety in children when facing dental fracture emergencies are by providing information about the steps of handling through education, the right media to use is booklet media. To determine the effectiveness of booklet media on attitudes in handling dental fracture emergency anxiety in elementary school children. This research is quantitative with a cross-sectional method with pre and post test design. The sample in this study was 27 5th grade elementary school children who were taken by total sampling. Data analysis was carried out using the Shapiro Wilk normality test and the Wilcoxon Test to test two paired samples. The results of the statistical test showed an increase in attitudes seen in the results of the Pre-Test and Post-Test scores with an average value of 70.00 to 89.19 with a P-Value = 0.000 (<0.05) it can be said that booklet media is effective in improving attitudes in handling emergency anxiety of tooth fractures. Booklet media is effective in improving attitudes in handling emergency anxiety of tooth fractures in elementary school children.